NILAI KETELADANAN K. H. AHMAD DAHLAN DALAM FILM TITIR (KAJIAN SEMIOTIKA): THE VALUE OF K. H. AHMAD DAHLAN'S EXAMPLE IN THE FILM TITIR (SEMIOTIC STUDY) - Rahmat; Mulkhan, Abdul Munir; Zamah Sari; Adelya Daniyah (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This article is about studying exemplary values ​​in the film Titir, which tells the story of KH. Ahmad Dahlan is a leading Islamic organization in Indonesia for the welfare of teachers and Muhammadiyah schools. The method used is qualitative by observing the Titir film using note-taking techniques. The approach used is Charles Sainsders Peirce's semiotic analysis by explaining the visual data depicted in the Titir film. This film not only provides a narrative story of struggle but also as a visual medium that conveys exemplary values ​​through the words and actions carried out between the characters. As a result, KH Ahmad Dalan's exemplary value was obtained. Ahmad Dahlan in the film Titir is leadership, love, and honesty.